Towards an Improved anti‐HIV Activity of NRTI via Metal–Organic Frameworks Nanoparticles. Issue 12 (17th June 2013) - Agostoni, Valentina; Chalati, Tamim; Horcajada, Patricia; Willaime, Hervé; Anand, Resmi; Semiramoth, Nicolas; Baati, Tarek; Hall, Shaun; Maurin, Guillaume; Chacun, Hélène; Bouchemal, Kawthar; Martineau, Charlotte; et al.
Abstract Nanoscale mesoporous iron carboxylates metal–organic frameworks (nanoMOFs) have recently emerged as promising platforms for drug delivery, showing biodegradability, biocompatibility and important loading capability of challenging highly water‐soluble drugs such as azidothymidine tryphosphate (AZT‐TP). In this study, nanoMOFs made of iron trimesate (MIL‐100) were able to act as efficient molecular sponges, quickly adsorbing up to 24 wt% AZT‐TP with entrapment efficiencies close to 100%, without perturbation of the supramolecular crystalline organization. These data are in agreement with molecular modelling predictions, indicating maximal loadings of 33 wt% and preferential location of the drug in the large cages. Spectrophotometry, isothermal titration calorimetry, and solid state NMR investigations enable to gain insight on the mechanism of interaction of AZT and AZT‐TP with the nanoMOFs, pointing out the crucial role of phosphates strongly coordinating with the unsaturated iron(III) sites. Finally, contrarily to the free AZT‐TP, the loaded nanoparticles efficiently penetrate and release their cargo of active triphosphorylated AZT inside major HIV target cells, efficiently protecting against HIV infection.